TEUNGKU MUHAMMAD DAUD BEUREUEH DAN REVOLUSI DI ACEH (1945-1950) - Bambang Satriya; Andi Suwirta; Ayi Budi Santosa (Universitas Pendidikan Indonesia dan APPS (Asosiasi Pendidik dan Peneliti Sejarah), 2018)
This research was distributed by attractions of authors to Teungku Muhammad Daud Beureueh the leader with big influence when the revolution happened in Aceh. The main issues studied in this research is “How was Teungku Muhammad Daud Beureueh’s role in defending the independence of Indonesian Republic in Aceh 1945-1950?”. This study uses historical method which includes four steps: 1) Heuristics, 2) Criticism, 3) Interpretation, 4) Historiography. Based on the result, the political and socio-economic conditions in Aceh after the independence of Indonesian Republic was unstable. The role of Teungku Muhammad Daud Beureueh in Peristiwa Cumbok gave the awareness to local government to give more attention in this horizontal conflict and he instructing to mobilize the troops to attack the uleebalang clan in Pidie. He also stopped the Tentara Perjuangan Rakyat (TPR) movement who headed by Husin Al Mujahid. As the Military Governor of Aceh, Langkat, and Tanah Karo, Teungku Muhammad Daud Beureueh can merged the paramilitary organizations into TNI organization, he also the inisiator who collected the cost to buy an airplane for Indonesian government, and he can stopped the Sayid Ali movement. Teungku Muhammad Daud Beureueh rejected the merging of Aceh into the Sumatera Utara Province and this case made his disappointed to the center government and also Soekarno.